Bevolking, vrouwen en milieu - De Keyser, Myriam; Miguet, Hugo; Vandenbergen, Isabelle (Brussel: Werkgroep Mundiale Vorming; NCOS, 1996)
"Myriam De Keyser; Hugo Miguet; Isabelle Vandenbergen... et al."